The Influence of Brand Image and Promotion on Consumer Purchase Decisions of Somethinc Products through the TikTok Shop Application - Mia Maulidia Putri; Fenni Supriadi (SAINTIS Publishing, 2025)
This study investigates the influence of brand image and promotion on consumer purchasing decisions for Somethinc skincare products through the TikTok Shop platform. Using a quantitative associative approach, data were collected through questionnaires from 100 respondents who met specific criteria. The analysis employed multiple linear regression, partial (t-test), and simultaneous (F-test) hypothesis testing, supported by classical assumption tests. The findings reveal that both brand image and promotion significantly influence purchasing decisions, with a regression model of Y = 1.413 + 0.370X₁ + 0.314X₂. The coefficient of determination (R²) value of 0.453 indicates that 45.3% of the purchasing decision variation is explained by the independent variables, while the remaining 54.7% is influenced by other factors. The t-test results show that brand image and promotion each have a positive and significant impact. These results suggest that a strong brand identity, supported by effective and adaptive promotional strategies via TikTok, is crucial in shaping consumer behavior. The study recommends that brands maintain a consistent image and continue leveraging social media platforms to engage young digital consumers. Future research is encouraged to include additional variables and explore other e-commerce platforms.